Level of Teacher’s Self Efficacy Based on Gender, Teaching Experience and Teacher Training - Yusof, Che' Mah; Md Nor, Mariani (American Scientific Publishers, 2017)
This study aimed to review the level of primary school teacher self-efficacy according to gender, teachers’ training and teaching experience that pursued. It involved 443 teachers primary school around the Federal District Kuala Lumpur, Malaysia which is selected by stratified random. The samples consist of 122 male and 321 female teachers. This study’s data were collected by using questionnaire method. Classroom Management and Discipline instruments Efficacy built by Emmer Hikman (1991) contains 35 items were used to collect data on Teachers Self Efficacy. SPPS apps version 22 is used to analyse survey data. The findings indicate that the level of primary school teacher self-efficacies was at a moderate level, M = 3.306, SP = 0.288, while findings also indicate that there are no significant differences according to gender self-efficacies of teachers and teacher training. However, the results show that there is a significant difference of efficiency of teachers according to their own teaching experience.